PERBEDAAN POLA MENSTRUASI ANTARA PEMAKAIAN ALAT KONTRASEPSI PIL DAN SUNTIK DI PMB HEROWATI PURWODADI - Nurul Kodiyah; Laily Himawati; Mun Aminah (Journal Of Applied Health Research And Development, 2020)
Background: The Family Planning service program is one of the choices made to regulate or limit the number of children they have. The pill is the most modern contraceptive method or method used in Indonesia after birth control. The selection of family planning devices based on information received found that less than half (44%) of users of modern contraceptive devices or methods said that they were told about the side effects or problems of the contraceptive devices or methods used (1). Objective: The purpose of this study was to identify and identify differences in menstrual patterns between birth control pills and injectors. Research Methods: This study is a comparative study with cross sectional design, sampling using purposive sampling on the acceptor of birth control pills and injections in PMB Herowati. Consists of two groups, pill acceptors and injection acceptors. Retrieval of data using a menstrual pattern questionnaire sheet for each pill and injection acceptor. Data analysis using chi square test. Results: Chi square test results on each pill acceptor and injector acceptor are p table <p value (0.36 <0.05), this means that Ho is rejected and Ha is accepted, which means that there are differences in menstrual patterns between the use of pill contraception and injection contraception. Conclusions: From the results of the above research it can be concluded that regular menstrual patterns if consuming contraception is appropriate and routine the way it is used.